Better Eating and Recovery: Addressing Food Insecurity at an urban Community Mental Health Center - Marydale DeBor , Marydale DeBor JD (International Journal of Psychosocial Rehabilitation, 2016)
This article describes a pilot program to improve diet and nutrition among low-income clients of an urban mental health center, including efforts to transform the overall food delivery system and culture, and the ‘Better Eaters Club’, a recovery oriented, hands-on intervention directly targeting clients with group based and one-on-one nutritional counseling. The article outlines the complexity involved in full-scale transformation of an institutional food delivery system and culture, and describes initial, promising results of the Better Eaters Club and one-on-one nutritional counseling, based on anecdotal reports from participants. This pilot project has laid an important foundation for a transformed food delivery system, and the institutionalization of a cooking and nutrition program designed specifically for low-income people with mental illness, including a finances and budgeting component. Future steps will incorporate more rigorous evaluation mechanisms tracking health indicators, knowledge of nutritional issues, cooking skills, and food security